Acute kidney injury in dogs: Etiology, clinical and clinicopathologic findings, prognostic markers, and outcome. (1st February 2022) - Rimer, Dar; Chen, Hilla; Bar‐Nathan, Mali; Segev, Gilad
Abstract: Background: Acute kidney injury (AKI) is a common, potentially fatal condition. Objectives: To characterize the etiologies, clinical and clinicopathologic findings, hospitalization period, and outcome of dogs with AKI and to identify markers of negative prognosis. Animals: Two hundred forty‐nine client‐own dogs diagnosed with AKI and hospitalized at a veterinary teaching hospital. Methods: Retrospective study. Search of medical records for dogs with AKI. Results: Common clinical signs included lethargy (225/249, 90%), anorexia (206/249, 83%), and vomiting (168/249, 68%). Etiologies included ischemic/inflammatory (144/249, 58%), infectious (19/249, 8%), nephrotoxicosis (14/249, 6%), or other (13/249, 5%). Hospital‐acquired AKI was diagnosed in 9% (23/249) of the dogs. Median presentation and peak serum creatinine (sCr) concentrations were 4 mg/dL (range, 1.1‐37.9) and 4.6 mg/dL (range, 1.1‐43.1), respectively. Dogs were classified to AKI grades as follows: Grade I, 6 (2%), Grade II, 38 (15%), Grade III, 89 (36%), Grade IV, 77 (31%), and Grade V, 39 (16%). One hundred and sixty‐four (66%) dogs survived. There was a positive association between death and AKI grade ( P  = .009). The case fatality rate was higher among dogs with anuria compared with dogs without anuria (50% vs 28%, respectively; odds ratio [95% confidence interval]: 2.5 [1.39‐4.6]; P  = .002). Forty‐seven (18.8%) dogs underwent hemodialysis, of which 60% survived. Conclusion and Clinical Importance: Two‐thirds of dogs with AKI survived. Hospital‐acquired AKI was common. The severity of AKI, as reflected by presence of anuria, AKI grade, and other body organs involvement, was associated with the outcome.